Stewardship Ecosystem Services Study: Carbon Stores on Florida Forest Stewardship Program Lands - Nilesh Timilsina; Francisco J. Escobedo; Alison E. Adams; Sonia Delphin (EDIS)
Nonindustrial private forestlands in Florida provide many environmental benefits, or ecosystem services. Ecosystem services are benefits from nature that are directly enjoyed, consumed, or used by humans, such as water quality improvement or protection, recreation, biodiversity, and even timber. Another benefit from forests that is gaining interest is their ability to store carbon through the photosynthetic capture of carbon dioxide, a greenhouse gas, in tree, plant, and soil biomass. The carbon dioxide that is stored over the life of a forest, called carbon stocks, is not only important for mitigating greenhouse gas contributions to climate change, but it can also be valued in several markets and incorporated into environmental policy instruments. This 5-page fact sheet was written by Nilesh Timilsina, Francisco J. Escobedo, Alison E. Adams, and Sonia Delphin, and published by the UF Department of School of Forest Resources and Conservation, October 2013. http://edis.ifas.ufl.edu/fr384